Efficient adaptive controllers and recursive filters for centralized control scheme of islanded microgrid with linear and non-linear loads. (October 2022) - Elnady, A.; Adam, A.A.; Nasir, M.
Highlights: A new centralized control scheme is presented to accurately stabilize the load voltage. A new centralized control scheme is presented to seamlessly share the load power among inverters. A new recursive filter is introduced to estimate the voltage harmonics and fundamental. The experimental results are obtained through the rapid control prototyping. Abstract: This paper presents a new combination of adaptive controllers and recursive filters for the operation of the microgrid with different balanced, unbalanced, and nonlinear loads. The suggested control scheme has the cascaded structure of voltage and current loops for positive- and negative-sequence control. The suggested adaptive controllers are the single-perceptron-based PI controller (the 1st adaptive controller) and the least mean fourth-based PI controller (the 2nd adaptive controller). The 1st adaptive controller is employed with the voltage control loop, while the 2nd adaptive controller is integrated with the current control loop. The Gauss-Newton algorithm is newly formulated to recursively estimate the voltage fundamental/harmonics at the load side. The suggested adaptive controllers are compared with other controllers for the same microgrid operation. The practical implementation of the suggested control scheme along with its adaptive controllers and recursive filters is validated using the dSPACE-SCALEXIO platform using rapid control prototyping.